(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the logical and communicative functions of hashtags, which we encounter daily in virtual communication. On social networks, hashtags do not merely indicate the topic of a text but serve as a bridge uniting thousands of users around a single idea. The article highlights the role of this symbol in our language, the meanings it carries, and its impact on our virtual speech from a linguistic perspective.